Fetomaternal outcome in pregnancy with HELLP syndrome - Shelat, Prachi M.; Vyas, Rupa C.; Shah, Sapana R.; Nathwani, Naimish D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: HELLP Syndrome is a serious complication of pregnancy induced hypertensive disorders. It is defined as a triad of hemolysis, elevated liver enzymes, and low platelet count (HELLP). Objectives of this study was to find out incidence of HELLP syndrome in pre-eclampsia, eclampsia and its overall incidence. To analyse the clinical profile of HELLP syndrome. To study maternal and perinatal outcome including morbidity and mortality. Methods: A retrospective study was conducted from July 2017 to September 2019 at a tertiary care center with inclusion criteria of abnormal peripheral blood smear, elevated liver enzymes (LDH, aspartate aminotransferase), and low platelet count. Results: HELLP syndrome was more common in younger age group (45%) and in primigravida (52.5%). Most of the patients presented at >36 weeks of gestation (40%) and most of the patients delivered by caesarean section (67.5%). Maternal complications were acute renal failure (27.5%), DIC (22.5%), maternal mortality (7.5%). Neonatal complications associated were intrauterine death (27.5%), prematurity (25%) and intrauterine growth retardation (15%). Conclusions: Thus, HELLP syndrome requires an early diagnosis and early initiation of treatment at tertiary care center with all the medical facilities available.